Tinjauan Kelancaran Klaim Pasien Covid-19 - Peter Herey; Nauri Anggita Temesvari (Poltekkes Kemenkes Semarang, 2022)
The increase of Covid-19 cases that occurred in Indonesia affected the financial system in healthcare facilities. One of the policies resulting from the increase of Covid-19 cases is that the Ministry of Health issued technical instructions for reimbursement of health service claims for hospitals that provide Covid-19 services. In the implementation of these rules, there are obstacles so that the claims submitted are delayed or not approved. The purpose of this study is to analyze Covid-19 claims approval in terms of input, process, and output components. The research method is cross-sectional with a quantitative descriptive approach. The research was conducted at Siloam Sentosa Hospital Bekasi by reviewing Covid-19 claims with data collection method was done using the document review. The instrument used is a document review sheet to identify policies and describe the approval of claims. The population in this study were all Covid-19 claims in January-February 2021. The sample was taken using a saturated sample with a total of 108 claims. The applications used for the claim process are INA-CBG and E-claims. In the implementation of claim submission, the hospital adopted the technical instruction for claim reimbursement issued by the Ministry of Health and has implemented it. The results of the study show that 63% of approved claims. The cause of the claim not being approved occurred in the process component where the difference of understanding from the coder so that it was not correct in coding, completeness of claim documents, and inconsistency in filling out medical records